2019
DOI: 10.1094/mpmi-02-19-0055-r
|View full text |Cite
|
Sign up to set email alerts
|

A Gain-of-Function Screen Reveals Redundant ERF Transcription Factors Providing Opportunities for Resistance Breeding Toward the Vascular Fungal Pathogen Verticillium longisporum

Abstract: Verticillium longisporum is a vascular fungal pathogen leading to severe crop loss, particular in oilseed rape. Transcription factors (TF) are highly suited for genetic engineering of pathogen-resistant crops, as they control sets of functionally associated genes. Applying the AtTORF-Ex (Arabidopsis thaliana transcription factor open reading frame expression) collection, a simple and robust screen of TF-overexpressing plants was established displaying reduced fungal colonization. Distinct members of the large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 58 publications
1
28
0
Order By: Relevance
“…Very recently, Xiong et al (2020) reported that a knockdown of GhWRKY70D13 improved cotton resistance to V. dahliae going along with up‐regulation of genes involved in ET and jasmonic acid (JA) biosynthesis as well as increased ACC, JA and JA‐isoleucine levels. Also, Arabidopsis ERF TFs are induced in response to V. longisporum and their over‐expression caused a reduction of fungal DNA within the mutants, while RNAi against ERFs had the opposite effect (Fröschel et al , 2019). But also the opposite effect has been observed with Arabidopsis etr1 mutants being more resistant to V. dahliae (Pantelides et al , 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, Xiong et al (2020) reported that a knockdown of GhWRKY70D13 improved cotton resistance to V. dahliae going along with up‐regulation of genes involved in ET and jasmonic acid (JA) biosynthesis as well as increased ACC, JA and JA‐isoleucine levels. Also, Arabidopsis ERF TFs are induced in response to V. longisporum and their over‐expression caused a reduction of fungal DNA within the mutants, while RNAi against ERFs had the opposite effect (Fröschel et al , 2019). But also the opposite effect has been observed with Arabidopsis etr1 mutants being more resistant to V. dahliae (Pantelides et al , 2010).…”
Section: Discussionmentioning
confidence: 99%
“…AtERF5, one of the closest orthologs to the VviERF6L clade, directly interacts with AtERF6 and 8 as well as SCL13 and MPK3 and 6 in unique combinations to respond differentially to Pseudomonas syringae [ 81 ], Botrytis cinera [ 77 ], Alternaria brassicicola [ 81 ] , and Meloidogyne incognita [ 82 ]. Aterf5/6 double mutants have enhanced susceptibility to V. longisporum , a fungus that induces severe wilting and plant death [ 83 ]. Another pathogen related example of a potential role in pathogen response shows decreased VviERF6L expression in response to Plasmopera viticola (downy mildew) in more susceptible vines and either an increase or no significant change in transcript abundance in more tolerant vines [ 84 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…AtERF5, one of the closest orthologs to the VviERF6L clade, directly interacts with AtERF6 and 8 as well as SCL13 and MPK3 and 6 in unique combinations to respond differentially to Pseudomonas syringae [81], Botrytis cinera [77], Alternaria brassicicola [81], and Meloidogyne incognita [82]. Aterf5/6 double mutants have enhanced susceptibility to V. longisporum, a fungus that induces severe wilting and plant death [83]VviERF6L expression in response to Plasmopera viticola (downy mildew) in more susceptible vines and either an increase or no significant change in transcript abundance in more tolerant vines [84,85].…”
Section: Vvief6ls Were Differentially Expressed In Response To Bioticmentioning
confidence: 99%